Efektivitas Sistem Informasi dalam Meningkatkan Kualitas Pelayanan Ruang ICU/ICCU (Studi Kasus pada Ruang ICU/ICCU RSUD Sultan Suriansyah Kota Banjarmasin): Penelitian - Supiati; Khuzaini; Dwi Wahyu Artiningsih; Zakky Zamrudi; Ana Sofia Herawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the effectiveness of SIMRS in improving service quality in the ICU/ICCU unit of RSUD Sultan Suriansyah Banjarmasin, its role in accelerating administrative processes and patient data management, and the obstacles encountered in its implementation. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving ICU nurses and pharmacy personnel as key informants. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that SIMRS is considered effective in improving ICU/ICCU service quality, as reflected by easier access to information, increased work efficiency, improved coordination among healthcare professionals, and enhanced support for clinical decision-making. SIMRS also contributes to faster administrative processes and patient data management. However, several obstacles remain, including network instability, delays in inter-unit data synchronization, and the lack of continuous system training.